CFD comparison of 2D and 3D aerodynamics in H-Darrieus prototype wake - Saïf ed-Dîn Fertahi; Abderrahim Samaouali; Imad Kadiri (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2023)
In the present study, a comparative assessment is conducted to evaluate the outcomes derived from two-dimensional (2D) and three-dimensional (3D) computational fluid dynamics (CFD) models utilizing the unsteady Reynolds-averaged Navier–Stokes (URANS) approach. The focus lies on the aerodynamic performance of the H-Darrieus vertical axis wind turbine, which has been the subject of numerous numerical investigations since 2010. The k−ω shear stress transport (SST) turbulence model is employed to replicate the flow structures evolving in the turbine wake.The maximum power coefficients attained through 2D and 3D modeling are reported as Cp=0.4016 and Cp=0.5734, respectively, at a tip speed ratio (λ) of 3.0976. The maximum 2D and 3D absolute errors, corresponding to the evaluation of the power coefficients, are determined to be 14.9714% and 29.1582%, respectively. These errors are calculated at λ=2.5183 and λ=3.0976. The parametric study conducted herein reveals that the range of the power coefficient enhancement, considering 3D aerodynamic effects, surpasses that obtained from 2D calculations. In 3D modeling, this range is delineated between λ=1.85 and λ=3.10, whereas, in 2D modeling, it is defined by the interval bounded by λ=2.05 and λ=3.10. The essential contours for comparing the 2D and 3D approaches and for characterizing the flow structures developing around the H-Darrieus turbine are generated and analyzed.